Outcomes of percutaneous vacuum‐assisted debulking of large vegetations as an adjunct to lead extraction. Issue 7 (31st May 2019) - Kiani, Soroosh; Sabayon, Dean; Lloyd, Michael S.; Hoskins, Michael H.; El‐Chami, Mikhael F.; Westerman, Stacy; Vadlamudi, Ratna; Keeling, Brent; Lattouf, Omar M.; Merchant, Faisal M.
Abstract: Background: Consensus statements on lead extraction give consideration to open surgical removal in the setting of large vegetations, to mitigate the risk of massive embolism that may occur with percutaneous lead removal. Vacuum‐assisted debulking (VD) of large vegetations as an adjunct to percutaneous lead extraction may provide an opportunity to mitigate these risks. Methods: We retrospectively identified all patients undergoing lead extraction at our institution for endovascular infection from 2012 to 2018 and stratified them into two groups based on presence of adjunctive VD (n = 6) or without VD (no‐VD, n = 39). VD was performed with the AngioVac system (Angio‐Dynamics, Latham, NY, USA). Results: Across the cohort, mean age was 62 ± 15 years, ejection fraction was 41 ± 16%, and 39% had end‐stage renal disease on dialysis. Defibrillator systems were present in 71%, and 22% had cardiac resynchronization devices. Mean duration of the oldest extracted lead was 6.3 ± 4.9 years. There were no significant differences in baseline covariates between groups. Those in the VD group were significantly less likely to have Staphylococcus aureus as a causative organism ( P = .04). In the VD group, vegetations targeted for debulking ranged in size from 1.8 to 6 cm (longest dimension). There were no operative deaths or clinically evident embolic events in either group. The overall nonfatal complication rate in the VD group was higher (33.3% vs 2.3%, P = .043). Conclusion: : VD can be performed as an adjunct to percutaneous lead extraction with a reasonable safety profile. The relative safety and efficacy of this approach removal requires further study.